Optimalisai Taman Baca Sebagai Wadah dntuk Meningkatkan Minat Baca Masyarakat Desa - Ach. Syaikhu; M Rafli Nur; Dedik Irawan; Faridatul Mufidah; Ani R (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
In line with the rapid advancement of technology, there has been a significant decline in reading interest across various age groups—both adults and children. One of the main contributing factors is the increasing addiction to digital devices, which has shifted attention away from reading activities and learning responsibilities at home. In response to this issue, we have initiated a movement aimed at revitalizing the spirit of literacy through the establishment and development of the Baitul Ilmi Community Reading Center located in Gesang Village. As an initial step, we have launched a book donation program, open to anyone who wishes to contribute books to support the sustainability of this literacy initiative. Based on our preliminary study, the primary target audience of this program includes children at the kindergarten and elementary school levels. To enhance their engagement and participation, we have adopted the field trip method as our key strategy. This method has proven to effectively increase children's enthusiasm and has received a positive response from the local community, particularly from parents. This initiative is also supported by various community stakeholders, including village authorities, the Family Welfare Empowerment Team (TP PKK), and the Gesang Village Youth Organization (Karang Taruna), all of whom are committed to fostering a culture of literacy from an early age to ensure a brighter future for the next generation.